A 2D Model for Interfacial Recombination in Mesoscopic Perovskite Solar Cells with Printed Back Contact. Issue 1 (25th November 2020) - Wagner, Lukas; Qiu, Cheng; Unmüssig, Moritz; Bogachuk, Dmitry; Mastroianni, Simone; Würfel, Uli; Hu, Yue; Han, Hongwei; Hinsch, Andreas
Abstract : A physical model to explain the 2D charge recombination in mesoscopic graphite‐based perovskite solar cells (PSCs) having a highly selective front electrode and a nonselective back electrode is presented. Steady‐state photovoltage and photoluminescence (PL) as well as transient PL are studied for a wide range of device configurations, providing insights in the interface recombination at the front and back contact, namely, the mesoporous titania (m‐TiO2 ) and the graphite layer. Combining experimental evidence with the first 2D simulation of a perovskite solar cell, it is found that the characteristic thick absorber layer of mesoscopic graphite‐based PSC is a necessity to enhance the photovoltage. This is because the interface recombination at the back contact is a diffusion‐limited process. The electrode spacing should, however, not be enhanced by increasing the perovskite/m‐TiO2 thickness as this increases surface recombination losses at this interface. The study determines design rules for the optimal geometry of the mesoporous layers and helps to identify the limiting recombination pathways for an improvement of future device architectures. Abstract : Comprehensive experimental and theoretical evidence is presented to elucidate the charge carrier recombination in mesoscopic perovskite solar cells (PSC). The spatially decoupled electron and hole migration inside the nanoporous charge extraction scaffold is examined by a 2D electrical model that explains the remarkably high photovoltages achieved in hole extraction layer‐free, carbon–graphite‐based PSCs.